A mathematical model for the dynamic simulation of low size cogeneration gas turbines within smart microgrids. (15th January 2017) - Bracco, Stefano; Delfino, Federico
Abstract: Microturbines represent a suitable technology to be adopted in smart microgrids since they are characterized by affordable capital and maintenance costs, high reliability and flexibility, and low environmental impact; moreover, they can be fed by fossil fuels or biofuels. They can operate in cogeneration and trigeneration mode, thus permitting to attain high global efficiency values of the energy conversion system from primary energy to electrical and thermal energy; from the electrical point of view, microturbines can operate connected to the distribution grid but also in islanded mode, thus enabling their use in remote areas without electrification. The paper describes the mathematical model that has been developed to simulate in off-design and transient conditions the operation of a 65 kWel cogeneration microturbine installed within a smart microgrid. The dynamic simulation model is characterized by a flexible architecture that permits to simulate other different size single-shaft microturbines. The paper reports the main equations of the model, focusing on the architecture of the simulator and the microturbine control system; furthermore the most significant results derived from the validation phase are reported too, referring to the microturbine installed in the Smart Polygeneration Microgrid of the Savona Campus at the University of Genoa in Italy. Highlights: Dynamic simulation model of a cogeneration microturbine. Off-design and transient performances of the microturbine. Simulator validated on the Smart Polygeneration Microgrid at the Savona Campus.